STUDI KASUS TENTANG SISWI YANG MEMILIKI KONSEP DIRI NEGATIF PADA KELAS X SMA MUJAHIDIN PONTIANAK TAHUN 2017 - Ningsih, Dwi Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research entitled case study about student who have negative self concept in class X SMA Mujahidin Pontianak. Common problem in this research is how effort to help student having negatif self concept in class X SMA Mujahidin Pontianak? As for the sub-problems: 1) How are the characteristics of student who have negative self concept?, 2) What psychological factors that cause student to have negative self concept?, 3) What physiological factors that cause student to have a negative self concept?, 4) What are the sociological factors that cause student to have a negative self concept?, 5) What are the efforts of help done to overcome the student who has negative self concept? The approach used in this reaserch is qualitative by using descriptive method. The research form is a case study. Data collection techniques used are direct observation, interviews and home visits. Based on observations and interviews with case subjects concluded that the identification of student problems are as follows: 1) psychological factors; a) thoughts, b) feelings, and c) emotions. 2) physiological factors; case subject have a lack of vision in reading writing. 3) sociological factors; case subject are children who are not very active in social relationships with school friends, tend to be quiet in communicating.Keywords: Student who have negative self concept